ANOMALI BRAINROT: TAFSIR BUDAYA ATAS TUBUH, HASRAT, DAN KEKERASAN SIMBOLIK DI ERA DIGITAL - Maknun, Moch Lukluil; Muzayanah, Umi; Santoso, Arif Gunawan (HISKI, 2025)
AbstractThe Anomali Brainrot phenomena on social media tergeting generation Z and Alpha in early 2025 raises serious concern. Despite apperaring as a platform for entertainment and creative expression, this phenomenon conceals threats to young individuals -ranging from esyptoms of psychological disordes to tendencies toward subversive behavior. Employing a systematic review of web-based literacy sources and scholarly journal articles, this study applies metadata analysis to describe brainrot as a sociocultural anomaly. Concepts such as discourse deconstruction, power relations, play of meaning, hyperreality, and identity representation are used to frame and interpret the findings. The analysis supports the hypothesis that brainrot represents a significant threat in the posthumanist era. A collective awareness involving parents, educational institutions, and govermental agencies is essential to respond to this phenomenon wiselt and responsibly.Keywords: posthumanism, hyperreality, anomaly, brainrot, culture AbstrakFenomena Anomali Brainrot di media sosial yang menyasar generasi Z dan Alpha di semester pertama 2025 mengkhawatirkan. Tampilan yang seolah hiburan dan wadah kreativitas nyatanya menyimpan ancaman bagi anak baik dari sebuah simptom penyakit psikologis hingga mengarah pada tindakan subversif. Menggunakan metode kajian literasi web dan artikel jurnal, kajian ini melakukan pembacaan sistematis dengan prinsip kerja analisis metadata untuk mendeksripsikan fenomena brainrot sebagai anomali sosial budaya. Konsep dekonstruksi wacana, relasi kuasa, permainan makna, hiperrealitas, dan representasi identitas digunakan untuk mendiskusikan dan menganalisis temuan. Hasil analisis menguatkan hipotesis bahwa anomali brainrot ini merupakan ancaman di era post humanisme. Diperlukan kesadaran bersama untuk dapat menyikapinya dengan bijak baik dari orangtua, instansi pendidikan, hingga pemerintah.Kata Kunci: post humanisme, hiperrealitas, anomali, brainrot, budaya